2019
DOI: 10.1007/s00253-019-10057-0
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium bovis BCG in metastatic melanoma therapy

Abstract: Melanoma is the most aggressive form of skin cancer, with a high mortality rate and with 96,480 new cases expected in 2019 in the USS. BRAF V600E , the most common driver mutation, is found in around 50% of melanomas, contributing to tumor growth, angiogenesis, and metastatic progression. Dacarbazine (DTIC), an alkylate agent, was the first chemotherapeutic agent approved by the US Food and Drug Administration (FDA) used as a standard treatment. Since then, immunotherapies have been approved for metastatic mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 163 publications
(156 reference statements)
0
16
0
Order By: Relevance
“…In high-income countries, several studies from Europe and the USA suggest that admission to hospital for unrelated infections may be reduced by live measles vaccine and BCG vaccine but increased by non-live DTP vaccine 9,10 . Evidence from high-income countries also indicates that BCG vaccination may reduce the severity of allergy 11 , malignancy [12][13][14] , diabetes 15 and Alzheimer disease 16,17 .…”
Section: Peter Aaby and Christine Stabell Bennmentioning
confidence: 99%
“…In high-income countries, several studies from Europe and the USA suggest that admission to hospital for unrelated infections may be reduced by live measles vaccine and BCG vaccine but increased by non-live DTP vaccine 9,10 . Evidence from high-income countries also indicates that BCG vaccination may reduce the severity of allergy 11 , malignancy [12][13][14] , diabetes 15 and Alzheimer disease 16,17 .…”
Section: Peter Aaby and Christine Stabell Bennmentioning
confidence: 99%
“…Intratumoral immunotherapy has been used in melanoma in which the approach to skin visible tumor is simpler. BCG was used in locoregional immunotherapies and metastasis melanoma (38). Mycobacterium bovis Bacillus Calmette-Guerin (BCG) serves as an adjuvant therapy that induces the recruitment of natural killer NK, CD4 + , and CD8 + T cells and contributes to antitumor immunity.…”
Section: Melanomamentioning
confidence: 99%
“…BCG can be administered in combination with chemotherapeutic and immunotherapeutic agents thus increasing the immune response and improving patient survival in melanoma patients. Since early trials BCG based immunotherapy for melanoma consistently showed a trend toward improved clinical outcomes in patients treated with BCG compared with observation alone (40). Other types of immunotherapy have been trained in this type of tumor.…”
Section: Melanomamentioning
confidence: 99%
“…Attempts are being made to treat melanoma with recombinant BCG strains [ 91 ]. The most successful were BCG variants expressing interleukin-2 (rBCG-IL-2) and granulocyte-macrophage colony stimulating factor (rBCG-GM-CSF).…”
Section: Introductionmentioning
confidence: 99%